BACKGROUND KNOWLEDGE IN INTERCULTURAL COMMUNICATION OF MEDIA SPANISH AND UKRAINIAN LANGUAGES - Bokova, Polina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article examines the phenomenon of background knowledge, its place and role in the process of intercultural communication. The current stage of development of the world community opens up new opportunities for cultural and intercultural communication, which today is interpreted as communication between representatives of different cultures, involves mutual understanding of the participants of the communicative act belonging to different national cultures. It is also noted that there are a certain number of problems between representatives of different cultures and speakers of different languages, which are directly related to the most important component of intercultural communication, which includes the languages and cultures involved in this process. Culture is a set of material and spiritual values accumulated in one or another national community that are absent in another or significantly different from them, make up the national socio-cultural fund, which is reflected in the language. Background knowledge is considered as socio-cultural information that is characteristic of a certain nation, learned by the mass of its representatives and reflected in the language of this national community. They are a key component of our perception, they actually precede knowledge about the subject and help to obtain new information about it, and serve as a factor in overcoming the linguistic and cultural barrier in intercultural communication. Thus, background knowledge is presented as a set of ideas about what makes up the real background against which the picture of the life of another country, another people un folds. ________________ References: • Karazeva, Y. A. «Otrazhenie natsionalno culturnoi spetzhifiki v hudozhestvenom texte (na materiale ispanoyazichnoi literaturi).» Sovremenie nauchnie isledovania i inovatsii (2012), http://vveb.snauka.ru/issues/2012/02/7920. • Manakin, M. Mova s mizhkulturna comunikatsia (Kyiv: Akademia, 2012), 288.